Inhibition of Taq DNA polymerase by catalpol. - Pungitore, Carlos Rodolfo (2004)
DNA polymerases have recently emerged as important cellular targets for chemical intervention in the development of anti-cancer agents. This report describes a PCR assay as a method to investigate the action mechanism of the inhibition of Taq DNA polymerase by catalpol. This inhibition was not primer or template specific, nor was it due to chelation of Mg2+ ions. In assays of hyperchromicity of double-stranded DNA, catalpol did not affect melting profile. The inhibitory effect of catalpol does not appear to depend on DNA concentration. In contrast, increasing dNTP concentration rescue the Taq DNA polymerase activity, suggestingthat catalpol acts in a competitive way with dNTPs at the binding site of the enzyme. Theoretical calculations reinforce the experimental data and the proposed mode of action of catalpol.